Anti-Inflammatory And Antipyretic Activity Of Faloak Stem Bark (Sterqulia Quadrifida, R.Br) In Dpt-Hb Vaccine-Induced Mice - Stefany S.A Fernandez; Dominus Nbunga; Acacio C Amaral; Stefany Selebele (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Faloak Bark (Sterculia quadrifida) has traditionally been used in East Nusa Tenggara to treat various diseases. Its secondary metabolites, including alkaloids, flavonoids, saponins, steroids, and terpenoids, have been identified as bioactive compounds. This study aims to evaluate the potential of Sterculia quadrifida Bark (SQ) as an anti-inflammatory and antipyretic agent. Male Swiss Webster mice were used as test subjects after acclimatization. Two samples were used in this study: Ethanol Extract of Sterculia quadrifida (EESQ) for anti-inflammatory testing and Ethyl Acetate Fraction of Sterculia quadrifida (FESQ) for antipyretic testing. This study involved five groups: negative control (CMC), positive control of Diclofenac Sodium (SD, 6.5 mg/KgBw) and Paracetamol (PCT, 65 mg/KgBw), and test group receiving EESQ at doses of 100, 200, and 400 mg/KgBw, and FESQ at doses of 50, 100, and 200 mg/KgBw. This study confirmed the presence of alkaloids, flavonoids, tannins, and saponins in Sterculia quadrifida. Both EESQ and FESQ showed anti-inflammatory and antipyretic effects comparable to the positive control, starting at doses of 200 mg/KgBw and 50 mg/KgBw, respectively. Higher doses showed more substantial antipyretic and anti-inflammatory effects. These findings suggest that SQ bark has the potential to be developed into an effective traditional medicine for treating fever and inflammation. Further studies are needed to confirm its efficacy and safety in humans for chronic use.